AB1209 THE RHEUMA-BUS-TOUR: TWO WEEK OPEN-ACCESS SCREENING FOR EARLY RHEUMATIC DISEASES. (June 2019) - Dreher, Matthias; Sauer, Julia; Scharm, Nicolas; Plagemann, Thomas; Assmann, Gunter; Hoeper, Kirsten; Triantafyllias, Konstantinos; Schmitt, Reinhold E.; Schwarting, Andreas
Abstract : Background: Early diagnosis is crucial for patients with rheumatic diseases. Studies show that early stage patients already show reduced mental and physical health [2, 3]. However, early diagnosis is often delayed due to the severe lack of rheumatologists in Germany. Objectives: The cross-sectional study compares data on physical and mental health of known and suspected early rheumatic patients, collected from participants of the bus tour. Methods: The Rheuma-Bus-Tour is an annual, two week open-access screening event in three states (Rhineland-Palatine, Saarland, Lower Saxony) that raises awareness for rheumatic diseases and identifies people with potential early cases of RA, SpA and PsA. All participants, regardless of their diagnosis status, completed a screening questionnaire about early symptoms, sociodemographic as well as physical and mental health parameters: Habitual Physical Activity Questionnaire (HPA) [1], Hannover Functional Ability Questionnaire (FFbh-R), Patient Health Questionnaire (PHQ-9), Well-Being Index (WHO-5). Additionally, a CRP on-site test and a medical consultation were offered. Results: In total, 853 participants completed the questionnaire, 214 with a known rheumatic diagnosis and 626 without one. Of 533 conducted CRP tests, 107 were positive. After the consultation, 58 patients were referred for an immediate rheumatologist appointment through the Rheuma-VOR network, 16 of which were diagnosed with RA, SpA, or PsA. Tables 1 and 2 present the group differences between the already diagnosed and the not diagnosed groups, split by CRP results. * Significant at p ≤ 0.05. Average age for all three groups falls in the 50-59 year range. Differences were found between PHQ-9, WHO-5 and FFbH-R, whereas none were found for HPA. Conclusion: As expected, a difference in mental health parameters was found for the "known diagnosis" and "no diagnosis+CRP negative" groups. The results also show differences for daily functional tasks between all three groups. However, the lowest scores were found for the group "no diagnosis+CRP pos", i.e. people with strong indications for an early rheumatic disease. This further supports evidence of reduced functionality for early stage patients and the need for early diagnosis and therapy. The lack of significant differences for HPA patterns could be caused by generally very low physical activity for all three groups. References: [1] Baecke JA, Burema J, Frijters JE (1982) A short questionnaire for the measurement of habitual physical activity in epidemiological studies. Am J Clin Nutr 36:936-942. [2] Branco JC, Rodrigues AM, Gouveia N, et al. (2016) Prevalence of rheumatic and musculoskeletal diseases and their impact on health-related quality of life, physical function and mental health in Portugal: results from EpiReumaPt- a national health survey. RMD Open 2:e000166. [3] Triantafyllias K, Leiß R, Dreher M, et al. (2019) Depressive Symptomatik bei früher rheumatoider Arthritis. Zeitschrift für Rheumatologie (in press). Disclosure of Interests: Matthias Dreher: None declared, Julia Sauer: None declared, Nicolas Scharm: None declared, Thomas Plagemann: None declared, Gunter Assmann: None declared, Kirsten Hoeper: None declared, Konstantinos Triantafyllias: None declared, Reinhold E. Schmitt: None declared, Andreas Schwarting Grant/research support from: GSK, Pfizer, AbbVie, Novartis, Roche, Speakers bureau: GSK, Novartis